STUDI PEMETAAN KEBIJAKAN PERHUBUNGAN JALAN DI INDONESIA - Achluddin Ibnu Rochim (Program Studi Doktor Ilmu Administrasi, FISIP, Universitas 17 Agustus 1945 Surabaya, 2019)
This Road Transportation Policy Mapping Study in Indonesia departs from the problem of road congestion which is the cause of various problems of inefficiency, time wastage, depression, increasing pollutants that are not environmentally friendly. The government as a regulatory agent is demanded to provide a policy solution to avoid this problem again. All the policies taken by the government are never enough to stop congestion. Vehicle volume continues to increase every time while the length and width of the road does not increase. This study formulates the question of how is the road transportation policy map in Indonesia? By using the library research method. The findings show that the road transportation policy in Indonesia includes various policies on Transportation Development, Operational Policy, Road Traffic and Transport Network Policy, Traffic Engineering Management Policy, Infrastructure Monitoring and Maintenance Policy. The study of road transportation policy mapping in Indonesia also produced findings that it turns out that in Indonesia there is already a road transportation policy sitematics which in an orderly manner is already in an orderly hierarchy, starting from the highest policy to the lowest policy, namely technical in the field. From the study of road transportation policy mapping in Indonesia produced findings that all existing road transport policy products include: a. Undang-Undang Nomor 14 Tahun 1992 concerning Road Traffic and Transportation; b. Undang-Undang Nomor 22 Tahun 2009 concerning Road Traffic and Transportation; c. Peraturan Pemerintah Nomor 34 Tahun 2006 concerning Roads; d. Peraturan Menteri Pekerjaan Umum Nomor: 13 /PRT/M/2011 concerning Procedures for Road Maintenance and Ownership; e. Peraturan Menteri Pekerjaan Umum Dan Perumahan Rakyat Republik Indonesia Nomor: 20/Prt/M/2016 concerning Organization and Work Procedures of Technical Implementing Units in the Ministry of Public Works and Public Housing.